2019
DOI: 10.1212/wnl.0000000000007998
|View full text |Cite
|
Sign up to set email alerts
|

High-dose methylprednisolone for acute traumatic spinal cord injury

Abstract: ObjectiveDue to the continuing debates on the utility of high-dose methylprednisolone (MP) early after acute spinal cord injury (ASCI), we aimed to evaluate the therapeutic and adverse effects of high-dose MP according to the second National Acute Spinal Cord Injury Study (NASCIS-2) dosing protocol in comparison to no steroids in patients with ASCI by performing a meta-analysis on the basis of the current available clinical trials.MethodsWe searched PubMed and Cochrane Library (to May 22, 2018) for studies com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 39 publications
1
98
0
1
Order By: Relevance
“…Several trials of neuroprotective agents for TSCI have failed, despite evidence from different TSCI animal models that the drugs are neuroprotective [49][50][51]. In 3 TSCI patients, we injected intravenously a 4-mg bolus of dexamethasone and found that little (~0.64%, based on area under the curve calculations) dexamethasone entered the injury site [52].…”
Section: Enhancing Drug Deliverymentioning
confidence: 99%
“…Several trials of neuroprotective agents for TSCI have failed, despite evidence from different TSCI animal models that the drugs are neuroprotective [49][50][51]. In 3 TSCI patients, we injected intravenously a 4-mg bolus of dexamethasone and found that little (~0.64%, based on area under the curve calculations) dexamethasone entered the injury site [52].…”
Section: Enhancing Drug Deliverymentioning
confidence: 99%
“…Liu et al 6 have brought to attention the use of methylprednisolone in acute traumatic SCI and concluded that high-dose methylprednisolone does not improve neurologic outcomes in acute traumatic SCI and may increase the risk of adverse events. They recommend against the use of this corticosteroid early after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Confounding occurs when the true association between an exposure and an outcome is distorted by the presence of another variable (i.e., the confounder). 16 Another strength of the Liu et al 6 meta-analysis was that an assessment of study quality was performed, although the quality score was not used in the meta-analysis. There are several techniques for incorporating quality scores in metaanalyses, including excluding studies of a certain quality, subgroup analyses by study quality, and incorporating quality scores as weights in the meta-analysis.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…The effectiveness of MP therapy in spinal cord injury patients has been clearly demonstrated. [23][24][25] Spinal cord injury can be divided into primary and secondary injuries-primary injury denotes the damage caused by external forces at the moment of insult 18 and secondary spinal cord injury denotes a cascade of damage after the primary injury including edema, ischemia, microcirculatory dysfunction, and severe inflammatory response; secondary injuries are usually more serious. 9 High-dose MP therapy can mitigate the secondary injuries by inhibition of inflammatory and pre-oxidative responses; although, high-dose MP therapy may carry a high risk for side effects including poor wound healing and/or gastrointestinal bleeding, the risk of such side-effects is not usually significant, 25 hence, high dose MP therapy carries a significant role in preventing further cord injury.…”
Section: Discussionmentioning
confidence: 99%